Mobile Computing Handbook - Ilyas, Mohammad (CRC Press, 2009)
The debut of small, inexpensive, yet powerful portable computers has coincided with the exponential growth of the Internet, making it possible to access computing resources and information at nearly any location at almost any time. This new trend, mobile computing, is poised to become the main technology driver for a decade to come. There are many challenges that make mobile computing a hot research and development area. Researchers, engineers, and practitioners need a comprehensive resource and reference to aid them in their quest to make the potential of this technology a reality.